Kebijakan Hukum Pidana Dalam menanggulangi Tindak Pidana Pendidikan - Suyahman, Suyahman (WIDYATAMA, 2011)
Kebijakan Hukum Pidana Dalam menanggulangi Tindak Pidana Pendidikan Â Â SuyahmanÂ Dosen Program Studi Pendidikan Pancasila dan Kewarganegaraan-Fakultas Keguruan dan Ilmu Pendidikan, Universitas veteran Bangun Nusantara SukoharjoEmail sym_62@yahoo.comÂ Abstract Â Educational criminal act is integrated part of common criminal act. In Indonesia, educational criminal act since 1945 to 2002 there is no certain determination that manages educational criminal act, just in 2003 the act No 20 year 2003 about national education system in Chapter X section 67-71 arranged about criminal determination related with educational criminal act. But, statement related with main concept about it cannot be found in that act, as well as in KUHP and another roles. This reality gives image that educational criminal act is unimportant thing, whereas if it investigated deeply, the access of it give larger influences toward essential and existence of Indonesia. Therefore, it should be effort the tackling of efficiency and effective educational criminal act. There are many tools to tackle educational criminal act. One of them is using criminal act. Related to the using of criminal act as tackling criminal act tool, there are many problems linked, like: how does the criminal act policy tackle the educational criminal act? How should criminal act policy in tackling educational criminal act in the future? Those problems are the main problem that should be answered in this research. Based on the main problems, this research can be done by using policy approach. The type of this research is descriptive research to explain current and future problem. This research belongs to literacy research with secondary data as the main data. The collecting data is using documentation method. Data is presented and analyzed qualitative, from juridical analyze based on interactive model that rotates four cycles that are data collection, data reduction, presentation and verification. The result shows that legislative policy in tackling educational criminal act by penal tool prevail at this time included in act No 20 year 2003 about national education system chapter X section 67 â section 71. In this act related to educational criminal act cannot be differential between criminal and violation, while specifically educational criminal act cannot be found in KUHP at this time. In educational criminal act determination the sanction toward educational criminal act agent is in the form of fine act and prison act. While administrative and additional sanction is not involved. Therefore, the essences and existences of educational criminal act develop both quantitative and qualitative as well as the limitation sanction in educational criminal act so it is very urgently certain act that discussed about educational criminal act. Legislative policy in tackling educational criminal act by peal tool in the future should be: (1) formulating act about educational criminal act, (2) in that act formulated about qualification between criminal and violence, (3) formulating the complete and representative sanction so that covered administrative sanction, prison act sanction and additional act sanction, by determinate the amount of fine act minimum.Â  Â Keywords: legislative policy in tackling educational criminal act